Optimalisasi Pengendalian Manajemen Aktiva Tetap dalam Meningkatan Efektivitas Penghitungan dan Penghapusan Aset Menggunakan Metode Straight Line dan Fuzzy Edas - La Sudarman; Poniasih Lelawatty; Sarimuddin Sarimuddin; Sariani Nur Zunais (SemanTIK : Teknik Informasi, 2024)
This study aims to optimize fixed asset management at Universitas Sembilanbelas November (USN) Kolaka Campus B through the application of the straight-line depreciation method and the Fuzzy EDAS method for asset disposal. The straight-line method is used to consistently calculate asset depreciation every semester, while Fuzzy EDAS assists in making objective decisions for asset disposal by considering various criteria, such as asset age, asset value, and asset condition. The research results show that the integration of these two methods enhances asset management efficiency, minimizes the risk of errors, and supports asset utilization optimization. This system has proven to help the university manage its fixed assets more effectively, thereby extending the economic life of assets that are still usable and eliminating assets that no longer provide value. This research is expected to serve as a model for other institutions in fixed asset management